Simple and Fail-safe Method to Transform Miniprep Escherichia coli Strain K12 Plasmid DNA Into Viable Agrobacterium tumefaciens EHA105 Cells for Plant Genetic Transformation - Beenzu Siamalube; Emmanuel Ehinmitan; Maina Ngotho; Justus Onguso; Steven Runo (Bio-Protocol)
Agrobacterium-mediated gene transformation method is a vital molecular biology technique employed to develop transgenic plants. Plants are genetically engineered to develop disease-free varieties, knock out unsettling traits for crop improvement, or incorporate an antigenic protein to make the plant a green factory for edible vaccines. The method’s robustness was validated through successful transformations, demonstrating its effectiveness as a standard approach for researchers working in plant biotechnology. It enables the introduction of foreign DNA into plant genomes. Conventionally, plant genetic transformation has relied on time-consuming, costly, and technically demanding procedures, such as electroporation and chimeric viruses or biolistic methods, which usually yield variable transformation efficiencies. This study presents a simple and fail-safe protocol that involves a modified freeze-thaw and heat-shock concoction method. This approach involves a streamlined plasmid miniprep procedure to isolate high-quality plasmid DNA from Escherichia coli K12 strain, followed by a target-specific transfer into A. tumefaciens EHA105 strain. The optimized method minimizes DNA degradation and maximizes uptake by Agrobacterium cells, making it a reproducible and accessible protocol for various genetic engineering applications. The transformation efficiency is consistently high, enhancing plasmid uptake while maintaining cell viability, requiring minimal specialized equipment and reagents. The proposed protocol offers significant advantages, including simplicity, reliability, and cost-effectiveness, positioning it as a valuable alternative to traditional techniques in the field of plant biotechnology.